KETIDAKADILAN GENDER DALAM NOVEL KENANGA KARYA OKA RUSMINI - Zahra, Afifah; Hayati, Yenni (Jurnal Bahasa dan Sastra, 2019)
This research aimed to describe of gender inequality to women in the novel Kenanga by Oka Rusmini. The type of this research was qualitative research by using analysis of descriptive method. The data of this research was novel Kenanga by Oka Rusmini. The technique of data collection was done through four stages: (1) read and understood the novel as a whole, (2) determined the character, (3) identified data related to the kinds of gender inequality, the factors of gender inequality, the impacts of gender inequality, and (4) inventorized of data based format inventory data. Based on results of study,it can be concluded that: (1) the types of gender inequality are marginalization, subordination, negative stereotype, violance and burden; (2) the factors of gender inequality are caste factor, patriarchy culture, culture, social and economy; (3) the impacts of gender inequality are psychology, the destroy of idealism and moral.Keywords: gender inequality, women, feminism